Impact of a three-week full leg cast immobilization on infant crawling kinetics and spatiotemporal parameters - Mark D. Geil (PLoS ONE, 2025)
Despite its importance in the development of mobility in infants, there is a general lack of quantified data on infant crawling, and a specific lack of understanding of crawling kinetics, which includes the relative weightbearing and force generation among the four limbs. Moreover, because of the difficulty of measurement and study design, there is no longitudinal quantification of the impact of a perturbation to typical development, such as limb immobilization. This study measured kinetic and spatiotemporal outcomes in a typically developing infant prior to a fracture that necessitated a long-leg cast that immobilized the left knee and ankle, while crawling with the cast, and again one day after cast removal, and two weeks post. The study utilized a pressure-sensing mat to generate outcomes. Crawling in the cast resulted in a 37% decrease in speed, a shift of weight toward the arms (toward the right arm in particular), and a shift from double and quadruple limb support toward triple limb support. Upon removal of the cast, the unweighting and limb support patterns persisted, while speed recovered and actually exceeded baseline. Triple limb support was 12% at baseline, 28% in the cast, and 32% immediately following cast removal. Two weeks later, the value had dropped back to 17%, while speed continued to increase following a linear trend vs. age. These data provide insight into an infant’s ability to reorganize crawling kinematics, and the persistence of that reorganization following remobilization.